A photovoice study of international students' acculturation experience regarding exercise in Singapore - Qu, Chuxi (Nanyang Technological University, 2024)
Singapore is a global educational hub for international students, but limited research explored the acculturation experiences of international students in Singapore. This study aims to identify the impacts of acculturation on international students’ exercise routine. An open-ended and qualitative methodology was employed, involving a Photovoice method and focus group discussions. Ten international students were invited to participate in two rounds of focus group discussions for a total of 90-120 min. It was found that all students became more physically active after they came to Singapore. Facilitators included cultural shift and environmental affordance. The shift in attention from study to sports under Singapore’s education system, Singapore’s sportive culture, and interest in cultural extension and transmission enabled students to engage in more physical activities. Additionally, the sports facility accessibility and motivation to travel in a scenic country also encouraged international students to develop exercise habits. The language and communication initiated through sports and exercise empowered international students to acculturate as well. Exercise was an important way for them to learn slang, exchange cultural information, and build support networks with locals. Some students experienced barriers in doing sports in Singapore, they found that starting to participate in sports was hard, and social exposure through sports was risky. Integration and Separation acculturation strategies were adopted by students. Singaporean colleges and universities should implement effective strategies to assist international students in developing long-term exercise behaviors in order to better adapt to the culture of Singapore.